PELATIHAN PEMANTAUAN PENCEMARAN BAGI MASYARAKAT DI BANTARAN DAS KALIGARANG 1,2 SEMARANG DENGAN METODE GEOLISTRIK - Supriyadi, Supriyadi; Hardyanto, Wahyu; Budiyono, Aris; Djuniadi, Djuniadi (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2016)
The background of this activity has occurred is water pollution in Kaligarang river. Therefore it is necessary efforts to protect the environment along the it. Exercising their activities consist of (1) Preparation, (2) Implementation, and (3) evaluation of the participants are young people in rural districts offense Sukorejo Gunungpati Semarang who live along the Kaligarang river who pass through the village. The event begins with a lecture about the pollution of the river and continued geoelectricity measurements at points predetermined. Geoelectricity measurement results obtained in the field of electric current and potential difference at the point of measurement points. Results showed that the participants in the activity have improved understanding of the geoelectric. It is characterized by the seriousness of the activity when participants perform geoelectric measurements, process data directly in the field. Based on the map sectional resistivity soil layer of field measurement data concluded that there has been a seepage of river water in the area Kaligarang community service activities but seepage is not cause contamination in the soil.